(untitled) (INNOVATIVE ECONOMY, 2021)
Horlachuk O.A. FEATURES OF CONDUCTING JUDICIAL ECONOMIC EXPERTISE WITH DOCUMENTARY EVIDENCE OF LACK OF INVENTORY Purpose. The aim of the article is consideration of the characteristic features of conducting judicial economic expertise with documentary evidence of the shortage of commodity and material assets according to the results of the inventory. Methodology of research. The theoretical and methodological basis of the study is the scientific works of economists, legislative and normative legal acts. The following general scientific methods are used in the research process: analysis and synthesis, generalization – to determine the method of conducting a complete and objective economic study by a forensic expert; abstract and logical – for the formation of conclusions and proposals. Findings. The essence of the shortage of inventory, the reasons for its occurrence and stages of enterprises and organizations, a set of general and special research methods, including methods of documentary verification used by forensic economic experts in documenting the shortage of commodity and material assets, is considered. The expediency of application of software products in practical work of experts-economists is substantiated, which is explained by automated accounting at the enterprises and the organizations which documentary materials in electronic form can be used in case of appointment by judicial investigative bodies of judicial economic examinations upon establishment of shortage of commodity and material assets. This will increase the effectiveness of their activities. Originality. The study of the peculiarities of conducting economic examinations to substantiate the shortage of commodity and material assets was further developed. Practical value. The proposed methods can be used in conducting this type of examination by economic specialists. Key words: inventory, inventory acts, inventory descriptions, shortage of commodity and material assets, materially responsible person.